The Impact of Perceived Stress and Coping Adequacy on the Health of Nurses: A Pilot Investigation - Timothy R. Jordan; Jagdish Khubchandani; Michael Wiblishauser (Nursing Research and Practice)
Stress and coping abilities influence the health and work performance of nurses. However, little is known about the combined influence of stress perception and perceived coping adequacy and its impact on the health of nurses. This study examined the relationship between stress, coping, and the combined influences of perceived stress and coping abilities on health and work performance. A valid and reliable questionnaire was completed by 120 nurses in a Midwestern hospital in the USA. In general, the nurses were not healthy: 92% had moderate-to-very high stress levels; 78% slept less than 8 hours of sleep per night; 69% did not exercise regularly; 63% consumed less than 5 servings of fruits and vegetables per day; and 22% were classified as binge drinkers. When confronted with workplace stress, 70% of nurses reported that they consumed more junk food and 63% reported that they consumed more food than usual as a way of coping. Nurses in the “high stress/poor coping” group had the poorest health outcomes and highest health risk behaviors compared to those in other groups. The combined variables of perceived stress and perceived coping adequacy influenced the health of nurses. Therefore, worksite health promotion programs for nurses should focus equally on stress reduction, stress management, and the development of healthy coping skills.